Mindfulness dan universal diverse orientation: Perbandingan generasi Z dan Y pada masyarakat Dayak Ngaju - Nugroho, Wasis Priyo; Pudjiati, Sri Redatin Retno (Jurnal Psikologi Ulayat, 2024)
Dayak Ngaju tribe have a "huma betang" philosophy that reflects tolerance for diversity. Tolerance in this study is explained in the universal diverse orientation construct which is reflected in the huma betang philosophy of Dayak Ngaju tribe. This study aims to examine the relationship between mindfulness and UDO in generation Z and generation Y of Dayak Ngaju tribe in Palangka Raya City and examine the differences between these two variables in generation Z and generation Y using the Langer Mindfulness Scale-19 and the Miville-Guzman Universality Diversity Scale-Short Form. In addition, this study also tested the differences between the two variables in generation Z and generation Y using the Independent Sample T-test. Based on the Pearson-correlation of 129 participants, a significant positive relationship was found between mindfulness and UDO. However, no significant difference was found between mindfulness and UDO in generation Z and generation Y. Based on these results, this study is expected to enrich literature on mindfulness and UDO, while also becoming a reference material for further research who wants to examine similar things regarding Indonesian culture.